Revision of Lepidonopsis humilis (Augener, 1922) and description of L. barnichae sp. nov. (Annelida: Polychaeta: Polynoidae) based upon morphological and molecular characters - Salazar-Silva, Patricia; Carrera-Parra, Luis Fernando (Zootaxa, 2014)
Lepidonopsis humilis (Augener, 1922) has been considered as an amphiamerican species, widely recorded in both the Grand Caribbean region and the Tropical Eastern Pacific. Based on type material and additional materials, L. humilis is redescribed herein and its distribution clarified and restricted. Furthermore, the identity of specimens from the Mexican Pacific is clarified and a new species L. barnichae sp. nov. is described. This species is characterized by conical macrotubercles with slightly curved tips; all elytra with a tuft of papillae on the surface, isolated from the marginal papillae; and the second segment dorsally projecting over the prostomium as a small lobe. Additionally, there is a 17.6% genetic divergence in the nucleotide sequence variation of COI between L. humilis and L. barnichae sp. nov., which supports the morphological differences observed. Thus, L. humilis does not have an amphiamerican distribution but is restricted to the Gran Caribbean region; whereas the specimens from the Tropical Eastern Pacific belong to the newly described species L. barnichae sp. nov. A key to the three known species of Lepidonopsis is included.